Duplex DNA barcoding allows accurate species determination of morphologically similar limpets (Patella spp.) from non-destructive sampling. (9th June 2016) - Ashton, Thomas J.; Kayoueche-Reeve, Meriem; Blight, Andrew J.; Moore, Jon; Paterson, David M.
Abstract : Accurate discrimination of two morphologically similar species of Patella limpets has been facilitated by using qPCR amplification of species-specific mitochondrial genomic regions. Cost-effective and non-destructive sampling is achieved using a mucus swab and simple sample lysis and dilution to create a PCR template. Results show 100% concurrence with dissection and microscopic analysis, and the technique has been employed successfully in field studies. The use of highly sensitive DNA barcoding techniques such as this hold great potential for improving previously challenging field assessments of species abundance.